MILAAP - crowdfunding for all : helping patients by facilitating philanthropy - Chandwani, Rajesh; M., Vimal Kumar; Singh, Jang Bahadur; Asthana, Sonal (London : Indian Institute of Management, Ahmedabad, 2024)
Milaap is a popular medical crowdfunding platform in India, enabling interaction between those who want to raise funds and those who want to donate. To achieve the critical mass Milaap had to increase the trust among the donors and ensure a higher success rate of the campaigns. Milaap provided two types of services: Do it Yourself (DIY), and Supported Campaigns (SC). Milaap charged 5% of the raised amount from the DIY campaigns and 15% of the raised amount from the SC. Overall the chances of success were high in the SC. The case explores the dilemma of type of service to be prioritized.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Crowd funding -- India -- Case studies